Adult Primary Spinal Epidural Extraosseous Ewing’s Sarcoma: A Case Report and Review of the Literature - Mark Bustoros; Cheddhi Thomas; Joshua Frenster; Aram S. Modrek; N. Sumru Bayin; Matija Snuderl; Gerald Rosen; Peter B. Schiff; Dimitris G. Placantonakis (Case Reports in Neurological Medicine)
Background. Extraosseous Ewing’s sarcoma in the spinal epidural space is a rare malignancy, especially in adults. Case Presentation. A 40-year-old male presented with back pain and urinary hesitancy. MRI revealed a thoracic extradural mass with no osseous involvement. He underwent surgery for gross total resection of the mass, which was diagnosed as Ewing’s sarcoma. He was subsequently treated with chemoradiotherapy. He remains disease-free 1 year after surgery. Review of the literature indicated only 45 previously reported cases of spinal epidural extraosseous Ewing’s sarcoma in adults. Conclusions. Extraosseous Ewing’s sarcoma in the spinal epidural space is a rare clinical entity that should be included in the differential for spinal epidural masses. Its treatment is multidisciplinary but frequently requires surgical intervention due to compressive neurologic symptoms. Gross total resection appears to correlate with improved outcomes.